Religious and Tolerant Attitudes of University Students: A Comparative Study - Rifa'i, Andi Arif (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2019)
This research on plurality was carried out toward two Indonesian state universities (PTN) students, namely IAIN Syaikh Abdurrahman Siddik Bangka Belitung and Bangka Belitung University. This research aimed at finding out an idea of how the attitude of these PTN students in Bangka Belitung in dealing with the plurality. This quantitative research found that IAIN students are more exclusive as far as the belief system is concerned. Whereas in the context of inclusiveness, IAIN students are more inclusive in the belief that every religion contains truth and UBB students hold the same opinion. Regarding the attitude of students, UBB students are more pluralist in terms of rejecting missionaries, while the students of the IAIN are more pluralist in terms of the purpose of the truth of each religious teaching. Moreover, UBB students are more universalist in their view that religions are different because of historical factors. While in the moderate category of 2.76%, there are no intolerant students. Based on the results of various tests (t-test), it is shown that there are significant differences between IAIN and UBB students.